HIGHER EDUCATION DURING TRANSITION TO DISTANCE LEARNING - Platonova, Raisa I.; Muskhanova, Isita V.; Levchenkova, Tatiana V.; Olesova, Marianna M.; Mikhina, Galina B.; Yahyaeva, Amina Kh.; Betilmerzaeva, Maret M. (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of our research was to study the reasons for the global popularization of mass online education, its ascension in terms of organizing education through the compelled transition to a distance format in all universities, and to build approximate forecasts of changes in higher education after the pandemic. It was interesting for us to analyse the process of complete replacement of the traditional educational format with distance learning, and how the teachers and students actively use online MOOC courses developed by other universities during the teaching sessions of universities. We also analyse how MOOC influenced the change in the traditional system of university education as well as how the dynamics of the number of students as learners has changed courses in online platforms. The leading research methods were theoretical analysis, review of scientific literature, information from internet resources, method of analysis of educational activities of higher educational institutions, and comparative analysis and interpretation of the results of the work. In the course of our study, we found that, in general, most higher education institutions were able to provide uninterrupted online education, and some of the teachers have improved or mastered their computer educational technologies for the first time. At the same time, problems have been identified that with all its wide functional capabilities, online learning is still inferior to offline learning: in terms of conducting laboratory work in engineering disciplines, organizing pedagogical practice for future teachers, research work, etc. Main difficulties for teachers are caused by: the inability to control students during the performance of credit work, to actualize Soft Skills, and incompatibility with online learning of academic disciplines rich in emotional, spiritual and moral views, feelings and beliefs. The practical significance of the article consists in the use of the obtained results and research materials in the organization and management of online and offline education in higher education institutions. The novelty of the study is that it analyses the situation of transition of the universities to distance education. Furthermore, it examines the problems of its implementation and the organization in terms of safety, physical and emotional isolation of students and teachers, as well as social inequalities in access to quality Internet connection and availability of modern computers. There is also a need for reformatting of the education system - optimal merging options for both online and offline formats of education.